2016
DOI: 10.1007/s12593-010-0028-1
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive Digital Papillary Adenocarcinoma in a Young Female—a Rare Presentation

Abstract: A 20 year old female presented with a recurrent soft tissue swelling over the medial aspect of proximal phalanx of left little finger. It had recurred one year after excision. There was no lymphadenopathy or bony involvement. Previous histopathology reports were not available. After excision histopathological diagnosis was aggressive digital papillary adenocarcinoma. Later Ray's amputation of little finger was planned. Aggressive digital papillary adenocarcinomas are rare sweat gland tumors which occur on hand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Digital papillary adenocarcinoma (DPA) is a rare cutaneous adnexal neoplasm with a distinctive predilection for digital extremities, particularly the fingers and toes and adjacent skin of the soles and palms 1–3 . Tumors most commonly present in adults, with White male predominance, and a mean age of 43 years, although DPA has also been reported in adolescents 4,5 . Clinically, DPA typically manifests as a small, solitary, and asymptomatic nodule; however, it may be accompanied by pain.…”
Section: Introductionmentioning
confidence: 99%
“…Digital papillary adenocarcinoma (DPA) is a rare cutaneous adnexal neoplasm with a distinctive predilection for digital extremities, particularly the fingers and toes and adjacent skin of the soles and palms 1–3 . Tumors most commonly present in adults, with White male predominance, and a mean age of 43 years, although DPA has also been reported in adolescents 4,5 . Clinically, DPA typically manifests as a small, solitary, and asymptomatic nodule; however, it may be accompanied by pain.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the confirmation of the diagnosis of DPA, immunohistochemical studies have shown that DPA is positive for S100 protein, and some express estrogen and/or progesterone receptor. 3 , 4 , 5 In a study which was done by Suchak et al, it was found that Ki67 proliferation index was ranging from 2% to 30%, whereas smooth muscle actin (SMA), calponin, and P63 stained the myoepithelial layer surrounding the glandular structure. 10 However, the presence of myoepithelial cells does not reflect the benign biological behavior of the tumor.…”
Section: Discussionmentioning
confidence: 99%
“… 4 Most tumors present as a slow‐growing solitary, nodular, and usually painful mass that is grossly cystic. 5 We report the case of a 64‐year‐old male with a DPA involving the fifth digit of the left hand.…”
Section: Introductionmentioning
confidence: 99%
“…Follow‐up information is available on five of six pediatric/adolescent cases of which two (40%) had recurrent disease. One showed local recurrence at 1 year that was treated by ray amputation and the other showed multiple local recurrences and distant metastases at different time points from 5 to 20 years from initial diagnosis . Completeness of the initial excision was not known in both patients with recurrent disease; but the second patient with multiple recurrences had significant mitotic activity in the primary tumor.…”
Section: Discussionmentioning
confidence: 99%